Chemical Composition and Organoleptic Properties of Emulsion-Type Lamb Meat Sausage with Different Fat Levels - Iswoyo Iswoyo; Juni Sumarmono; Triana Setyawardani; Adi Sampurno; Cornelius Hari Wibowo (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2022)
Various lamb-based processed products have become popular in many countries, including Indonesia that are well known for lamb satay, lamb curry, grilled lamb, and others. Processing lamb meat into sausages is a potential alternative to diversify lamb-based processed food. This study aims to develop a lamb-based processed product in form of emulsion sausage. We used mixed lamb meat and fat of Batur lamb (0, 5, 10, 15, 20 and 25%) that was coarsely ground and added with 2.0% salt, 0.5% dextrose, 0.5% garlic powder, 0.5% pepper powder, 0.3% paprika powder and 0.5% chili powder. Meat, fat, and other ingredients are mixed evenly and then put into collagen casings and measured 10-cm long. Next, the sausage was steamed for +45 minutes, then cooled and drained. We used an experimental method with a Completely Randomized Design (CRD) assigning 6 treatments and 4 replicates. The treatments included T0: Lamb sausage without fat; T1 : Lamb sausage + 5% fat; T2 : Lamb sausage + 10% fat; T3 : Lamb sausage + 15% fat; T4 : Lamb sausage + 20% fat and T5 : Lamb sausage + 25% fat. The observed characteristics of sausages were chemical content (moisture, protein, fat, and ash content) and organoleptic properties (preferred colour, aroma, texture, taste, and acceptability). F test (anova) results showed that the treatment had a significant effect (P<0.05) on the moisture, protein, fat, and ash content of lamb sausage, as well as on preference for colour, aroma, texture, taste, and acceptance of lamb sausage. The results showed that the addition of 10% lamb fat produced emulsion-type lamb sausage with the most optimal characteristics, containing 63.290% water, 15.245% protein, 12.518% fat and 2.536% ash. The preferred colour, aroma, texture, taste and acceptance have satisfied the neutral criteria.